Psychological and Pedagogical Bases of the Organization of Problem-based Education through Folk Songs - Yuldashevich , Ruziev Davron (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the psychological and pedagogical basis of the organization of problem-based education through folk songs, problem situations, psychological environment, methodological recommendations aimed at the organization of creative activity.